116 Serum immunoglobulin levels and infection risk in Phase 3 ofatumumab trials in relapsing multiple sclerosis. Issue 6 (27th May 2022) - Wiendl, Heinz; Seze, Jérôme de; Bar-Or, Amit; Correale, Jorge; Cross, Anne; Kappos, Ludwig; Selmaj, Krzysztof; Häring, Dieter; Su, Wendy; ,
Abstract : Objective: To assess the effect of ofatumumab vs teriflunomide on serum immunoglobulin (Ig) levels and evaluate potential association between decrease in IgM/IgG levels and infection risk. Methods: Serum IgM/IgG levels were monitored at baseline (BL), W4, W12, and every 12 weeks thereafter. Proportion of patients with IgM/IgG levels below the lower limit of normal ( Results: Mean IgM/IgG levels were within reference ranges over time. Over all post-BL visits, higher propor- tion of ofatumumab patients had IgM Conclusion: Reduction in serum IgM levels was observed over time, Ig levels predominantly remained above LLN. No decrease in IgG levels was reported within the observation period. There was no apparent association between decreased Ig levels and infections in ofatumumab-treated patients. Funding statement: This study was funded by Novartis Pharma AG, Basel, Switzerland. teresa.sawtell@novartis.com 83